Precarious (E)utopianism: Intersecting Precarity and Capitalism in Suniti Namjoshi’s Dangerous Pursuits - Syeda Shehnaz (Transcript: An e-Journal of Literary and Cultural Studies, 2025)
The contemporary Indian landscape is dominated by dystopian narratives with the rising concerns about the planetary havoc caused by modern capitalism. This essay examines Suniti Namjoshi’s Dangerous Pursuits (2022), consisting of three stories, as a significant literary intervention that recuperates the concept of ‘eutopianism.’ The analysis will primarily focus on the story “Bad People” as a eutopian text and draw insights from the other two texts, that is, “Heart’s Desire” and “The Dream Book.” Through the examination of the texts, it will be possible to explore how Namjoshi reimagines utopia within the constraints of a global capitalist crisis and environmental precarity. The article begins by interrogating the capitalist logic of the self-sufficient, invulnerable subject, which manifests itself in various hierarchical relationships. It is then possible to understand the depiction of alternate eutopian subjectivity against the capitalist ‘self.’ This will lead to a discussion on utopianism by engaging contemporary utopian theories such as ‘critical dystopia,’ and ‘critical utopia’ against the analyzed literary texts. In doing so, it will be possible to understand the ways in which Namjoshi’s Dangerous Pursuits diverges from contemporary utopianism and establishes what this paper will call ‘precarious eutopianism.’ This reading positions Dangerous Pursuits as a vital text for rethinking the role of literature in imagining not only more just and sustainable futures but also hope.